Co-Resident Grandparent: A Burden or a Relief? A Comparison of Gender Roles between Italians and Migrants - Trappolini, Eleonora; Rimoldi, Stefania Maria Lorenza; Terzera, Laura (Frontiers in Human Dynamics, 2021)
In the international literature is generally recognised the principal task of grandparents as helping their daughters or sons in providing childcare. Most of those studies analysed grandparental childcare on the whole population; they have focused little attention on co-resident grandparent(s), which turns out to be an understudied topic in the European context; and finally, most of them investigated the effect of childcare on grandparents’ health status. However, the elderly population can both provide and receive care. Using two Italian surveys released by the Italian National Institute of Statistics, the “Social Condition and Integration of Foreign Citizen (2011-2012)” and the “Multiscopo – Aspetti della vita quotidiana (2011)”, the study aims to analyse differences in grandparental childcare provided by co-resident grandparents between Italian and migrant households, considering both the role played by grandparents’ self-rated health (SRH) and gender. We identify four grandparents’ profiles by combining grandparents’ SRH and their attitude to look after their grandchild(ren). Subsequently, we apply multinomial logistic regressions and we compute average marginal effects to facilitate results interpretations. Results display that migrant co-resident grandparents are less likely to declare bad SRH and no-childcare, and are more likely to declare good SRH and to provide childcare than Italian grandparents. Moreover, when considering gender differences, the real role is revealed: we find that women have a higher probability to report poor health and care for their grandchild(ren) than man. Such findings illustrate first, that grandparents’ cohabitation is the difference resulting from the need for care and support to care; and second, in addition to migrant status and SRH, gender is a determinant of grandparents’ childcare: women look after their grandchild(ren) more than men, whatever their health status.